Personality as Predictor of Religious Commitment and Spiritual Beliefs: Comparing Catholic Deacons and Men in Formation. Issue 1 (2nd January 2017) - Ferrari, Joseph R.; Reed, Jordan; Guerrero, Mayra
ABSTRACT: Roman Catholic deacons ( n = 1, 349) and deacon candidates ( n = 202), completed online measures of personality dimensions (i.e., HEXACO-60), religious commitment, spiritual transcendence beliefs, social desirability, and demographic variables. Social desirability tendencies did not impact responding for deacons or candidates. For candidates and deacons, honesty–humility and extraversion personality dimensions were significant predictors of religious commitment, and extraversion and openness to experience were significant predictors of spiritual beliefs of connectedness to others. Moreover, for deacons but not candidates, all personality dimensions significantly predicted at least one religiosity or spiritual belief. Implications for Catholic deacons and candidates for ordination are discussed.